Removal of heavy-metal pollutants by white rot fungi: Mechanisms, achievements, and perspectives. (20th June 2022) - Chen, Lin; Zhang, Xuan; Zhang, Meng; Zhu, Yonghua; Zhuo, Rui
Abstract: White-rot fungi (WRF), a resource with potential environmental applications, are well known for their extensive organic compound degradation abilities. The unique oxidative and extracellular ligninolytic systems of WRF, that exhibit low substrate specificity, enable them to display a considerable ability to transform or degrade different organic pollutants in the environment. In recent decades, the application of WRF for environmental purposes has expanded with the accumulation of knowledge and advancements in heavy metal pollution remediation. Various WRF strains, including Phanerochaete chrysosporium, Pleurotus ostreatus, Ganoderma lucidum, Trametes versicolor, Irpex lacteus, Lentinus edodes, Coriolus versicolor, and Schizophyllum commune, have been reported to be able to remediate heavy metals such as Pb, Cd, Cr, Cu, Ni, Zn, and Hg. In this paper, we provide an overview of WRF mediated heavy-metal pollutants removal, review the recent achievements and progress in heavy metal remediation using WRF, and pay attention to the co-remediation of heavy metal and organic pollutants by WRF. The mechanisms of heavy-metal pollutants remediation by WRF are also discussed. Furthermore, we address the associated problems and future research prospects. Graphical abstract: Image 1 Highlights: Reviewed recent achievements and progress in heavy metal remediation using WRF. Co-remediation of heavy metal and organic pollutants by WRF is discussed. Addresses the associated problems and mechanisms in heavy metal remediation by WRF.